2012
DOI: 10.1080/15287394.2012.722184
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Mimetic 4-tert-Octylphenol Enhances Ige-Mediated Degranulation of Rbl-2H3 Mast Cells

Abstract: Allergic diseases such as asthma have been on the rise in recent decades. Environmental or occupational exposure to estrogenic synthetic chemicals is suspected to be a contributing factor, and previous experimental studies indicated that estradiol and some xenoestrogens increase allergic signaling responses, such as degranulation, in immune cells. In the current study, data showed that the estrogen mimetic 4-tert-octylphenol (4tOP) enhances immunoglobulin (Ig) E-mediated degranulation of mammalian mast cell li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 20 publications
(26 reference statements)
0
12
0
Order By: Relevance
“…Observations from the current study are in agreement with other reports indicating that physiologic levels of E2 (Zaitsu et al, 2007; Jensen et al, 2010) and progesterone (Jensen et al, 2010) can enhance the release of β-hexosaminidase (β-hex; a degranulatory enzyme) and LTC 4 from mast cells. Additionally, treatment of mast cells with other synthetic xenoestrogens including endosulfan, dieldrin, dichloro-diphenyl-dichloroethylene (DDE), nonylphenol, Aroclor 1242, Aroclor 1254, di-(2-ethylhexyl) phthalate, and 4- tert -octylphenol (Narita et al, 2007; Lee et al, 2011; Kennedy et al, 2012), at concentrations comparable to those used in the current study, increases β-hex release.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Observations from the current study are in agreement with other reports indicating that physiologic levels of E2 (Zaitsu et al, 2007; Jensen et al, 2010) and progesterone (Jensen et al, 2010) can enhance the release of β-hexosaminidase (β-hex; a degranulatory enzyme) and LTC 4 from mast cells. Additionally, treatment of mast cells with other synthetic xenoestrogens including endosulfan, dieldrin, dichloro-diphenyl-dichloroethylene (DDE), nonylphenol, Aroclor 1242, Aroclor 1254, di-(2-ethylhexyl) phthalate, and 4- tert -octylphenol (Narita et al, 2007; Lee et al, 2011; Kennedy et al, 2012), at concentrations comparable to those used in the current study, increases β-hex release.…”
Section: Discussionmentioning
confidence: 72%
“…Additionally, a higher prevalence of adult-onset asthma has been reported in patients undergoing hormone replacement therapy (Barr et al, 2004; Dratva, 2010). Lab-based approaches also indicate that estradiol, progesterone, and synthetic xenoestrogens can enhance mast cell degranulation (Narita et al, 2007; Zaitsu et al, 2007; Jensen et al, 2010; Lee et al, 2011; Kennedy et al, 2012), and since mast cells play a central role in atopic asthma, it has been hypothesized that widespread exposure to synthetic xenoestrogens (Yang et al, 2006; Phillips and Foster, 2008; Latini et al, 2010) may be contributing to the increased prevalence of asthma by enhancing mast cell activation.…”
Section: Introductionmentioning
confidence: 99%
“…More recent studies have shown that peaks in E2 during ovulation (Vrieze et al, 2003; Thornton et al, 2012) or hormone replacement therapy (Barr et al, 2004; Dratva, 2010) are associated with worsened asthma symptoms in women. Additionally, E2 (Zaitsu et al, 2007; Jensen et al, 2010), progesterone (Jensen et al, 2010), and other xeno-estrogens (Narita et al, 2007; Lee et al, 2011; Kennedy et al, 2012) are capable of activating human or rat mast cell lines in vitro in the absence of IgE crosslinking.…”
Section: Introductionmentioning
confidence: 99%
“…These methods also allow verification of the concentration of TCS in solution and quantification of the effects that chemicals, such as TCS, have on mast cell degranulation. This protocol can be used to assess the effects of a wide variety of chemicals on mast cell degranulation, such as suspected endocrine disrupting chemicals 55 , and can potentially be scaled up for high throughput screening. Additionally, other mast cell types may be used in this assay in future work.…”
Section: Discussionmentioning
confidence: 99%